Biochar is colonized by select arbuscular mycorrhizal fungi in agricultural soils - Patrick Neuberger; Carlos Romero; Keunbae Kim; Xiying Hao; Tim A. McAllister; Skyler Ngo; Chunli Li; Monika A. Gorzelak (Mycorrhiza, 2024)
Arbuscular mycorrhizal fungi (AMF) colonize biochar in soils, yet the processes governing their colonization and growth in biochar are not well characterized. Biochar amendment improves soil health by increasing soil carbon, decreasing bulk density, and improving soil water retention, all of which can increase yield and alleviate environmental stress on crops. Biochar is often applied with nutrient addition, impacting mycorrhizal communities. To understand how mycorrhizas explore soils containing biochar, we buried packets of non-activated biochar in root exclusion mesh bags in contrasting agricultural soils. In this greenhouse experiment, with quinoa ( Chenopodium quinoa ) as the host plant, we tested impacts of mineral nutrient (as manure and fertilizer) and biochar addition on mycorrhizal colonization of biochar. Paraglomus appeared to dominate the biochar packets, and the community of AMF found in the biochar was a subset (12 of 18) of the virtual taxa detected in soil communities. We saw differences in AMF community composition between soils with different edaphic properties, and while nutrient addition shifted those communities, the shifts were inconsistent between soil types and did not significantly influence the observation that Paraglomus appeared to selectively colonize biochar. This observation may reflect differences in AMF traits, with Paraglomus previously identified only in soils (not in roots) pointing to predominately soil exploratory traits. Conversely, the absence of some AMF from the biochar implies either a reduced tendency to explore soils or an ability to avoid recalcitrant nutrient sources. Our results point to a selective colonization of biochar in agricultural soils.